Le polar, du fait divers au fait d’histoire - Véronique Desnain (Itinéraires)
The novels of Didier Daeninckx and Dominique Manotti include in their fictional narratives elements which appear to correspond to Barthes’ definition of the fait divers as an event which is unique and whose meaning is self-contained. Yet as the plot progresses, links are made between those elements to create a new narrative which calls into question not only our understanding of specific historical events, such as the October 1961 demonstrations in Paris, but also our very perception of official historical discourse.